Character Values: What Are They and How They Are Integrated in English Textbook Texts? - Utami, Putri Ayu Imayatul; Rohmatillah, Rohmatillah; Kholid, M. Ridho (English Education: Jurnal Tadris Bahasa Inggris, 2021)
This study is based on the issue of character value, which has recently spread out as many as social problems in Indonesia, as well as the phenomena around us that many inappropriate textbooks contents. Character values should be incorporated into teaching and learning materials. It is also related to the government regulation that requires the inclusion of the character values proposed by the Ministry of National Education as character building in all elements of education. The aim of this study was to examine the character values found in the texts as well as the strategies used in integrating character values in the texts of Erlangga’s English textbook for Senior High School Grade XI. This study applied qualitative research with a content analysis approach. The data source was English textbook Pathway to English, and the data were 19 texts gathered by reading and taking notes on texts in English textbook. The research findings revealed that the character values which are found in the 19 texts of English textbook being analyzed covers 16 character values proposed by the Ministry of National Education and the strategies of delivering character values in the texts consisted of two forms, explicit and implicit strategy.  Keywords: Character values, character values integration, English textbook, texts